'I'm a genuine Italian, but not a genuine Italian': Complex and shifting strategies of ethnic and moral boundary making in the narratives of Italian minority parents in Flanders. (May 2019) - Clycq, Noel
It is well-documented in (ethnic) identity research that individuals to a large extent construct an identity they feel comfortable with. However, this is not an easy task and one's identity is, for some more than for others, under constant pressure to be reflected upon and reconstructed. At the same time many individuals often feel that there is a core element in their (ethnic) identity that does not change and remains stable. Based upon 13 in-depth interviews with Italian origin parents in Flanders, this article discusses what might be a constant mechanism underlying identification processes for this group of individuals: the presentation of the self as morally good and valuable. However, to be able to do this, the Italian origin participants in this study have to develop a variety of sometimes contradictory strategies. In a Flemish society where their Italian ethnicity is not questioned or problematized, the participants seem very keen to underline how ethnically different from the Flemish-Belgian majority they are. Yet, at other times they present themselves as much more similar to this majority group when discussing other minority groups, in particular Muslims. However, the most striking group reconstruction occurs when participants use the example of 'genuine Italians' to differentiate themselves from a specific group of Italians, while at the same time stressing they are genuine Italians themselves. When studying these various strategies from the perspective of presentation of the self as morally good and valuable, it becomes clear why these seemingly contradictory strategies do not at all feel contradictory to the participants. The findings show how strong the need for such a recognition of the self is.